Heavy metals accumulation in mangrove, Rhizophora apiculata blume from Sepang River, Selangor. - Ramsie, Siti Aishah; Zulkifli, Syaizwan Zahmir (2012)
Bagan Lalang mangrove forest has been polluted by heavy metals contamination originated mainly from human activities. Despite of their significant importance in the estuary and coastal areas, it has been overexploited and unsustainable managed in large areas. The increase of waste discharges from residential, agriculture, manufacturing industries, animal farms etc along Sepang River eventually will deposit in mangrove area in estuary and coastal areas. Rhizophora apiculata was identified as one of the common mangrove species dominating Bagan Lalang mangrove area. In present study, sediments and mangrove tissues (matured and young stilt roots, leaves, and stems) were collected from a sampling site. The samples were analyzed for degree of metals accumulation using Atomic Absorption Spectroscopy (AAS). The highest metal concentration in sediment was Pb (49.29±1.59 μg/g) followed by Cu (39.86±6.72 μg/g), Ni (15.72±0.13 μg/g) and Cd (0.97±0.13 μg/g). The highest metal concentration in mangrove tissues were found in matured stilt root where Pb (52.06 ± 5.17 μg/g), Cu (19.22 ± 4.33 μg/g), Ni (5.83 ± 4.99 μg/g) and Cd (1.54 ± 0.08 μg/g). There was no significant difference of heavy metals concentrations between matured and young stilt roots (p<0.05). Based from the study, the lowest metal concentration was in leaves with Pb (9.63 ± 0.61 μg/g) followed by Cu (5.23 ± 1.73 μg/g), Ni (0.89 ± 0.25 μg/g) and Cd (0.18 ± 0.09 μg/g). Data from this study is important to evaluate the habitat quality recovery of mangrove ecosystem along Sepang River after heavy pollution in late 1990s.